Efeito de resinas modeladoras sobre as propriedades de superfície de um compósito resinoso - Almeida, Leonardo de (2023)
This study aims to evaluate the effect of modeling resins on composite resin surface properties (color stability, roughness, and hardness). Materials and Methods: Fifty-six discs of Empress Direct - Ivoclar Vivadent were produced from a silicone mold (2 mm in height and 5 mm in diameter), treated or not in the top layer with a modeling material [(none/control (mN), Composite Wetting Resin/Ultradent (mW), Modeling Resin/Bisco (mR), and Signum Liquid/Kulzer (mS)], and finished/polished or not [(polished (P) and not polished (nP)]. These discs were exposed to a coffee solution for 15 minutes/day for 21 consecutive days. Color variation (ΔE*) and initial and final hardness (D, D') and roughness (Ra, Ra') values were assessed. Results: All groups adopted an increase in ΔE of 3.3 regardless of surface treatment, however the groups that were polished had a smaller distance from the reference. For the roughness, for the mS modelers there was an equivalent roughness between the times, while for the mR group there was a greater roughness without polishing, diverging from the result of the mW that obtained a lower roughness when not polished. The microhardness changed in relation to the type of styler, and the highest hardness was found in the mR and mS group after polishing, mW after immersion obtained the best hardness result. Conclusion: The use of modeling liquids for composite resins can interfere with the surface properties, requiring discernment in choosing and avoiding excessive use.